Answer:
m = 2
General Formulas and Concepts:
<u>Pre-Algebra</u>
Order of Operations: BPEMDAS
- Brackets
- Parenthesis
- Exponents
- Multiplication
- Division
- Addition
- Subtraction
Equality Properties
Step-by-step explanation:
<u>Step 1: Define Equation</u>
m - 4m = -6
<u>Step 2: Solve for </u><em><u>m</u></em>
- Combine like terms: -3m = -6
- Divide -3 on both sides: m = 2
<u>Step 3: Check</u>
<em>Plug in m into the original equation to verify it's a solution.</em>
- Substitute in <em>m</em>: 2 - 4(2) = -6
- Multiply: 2 - 8 = -6
- Subtract: -6 = -6
Here we see that -6 does indeed equal -6.
∴ m = 2 is the solution to the equation.
Answer:
36 sq. cm
Step-by-step explanation:
triangle area= 0.5 * 12* 10
rectangle are= 8* 3
60 - 24 = 36
Simplifying
2c + 3 = 3c + -4
Reorder the terms:
3 + 2c = 3c + -4
Reorder the terms:
3 + 2c = -4 + 3c
Solving
3 + 2c = -4 + 3c
Solving for variable 'c'.
Move all terms containing c to the left, all other terms to the right.
Add '-3c' to each side of the equation.
3 + 2c + -3c = -4 + 3c + -3c
Combine like terms: 2c + -3c = -1c
3 + -1c = -4 + 3c + -3c
Combine like terms: 3c + -3c = 0
3 + -1c = -4 + 0
3 + -1c = -4
Add '-3' to each side of the equation.
3 + -3 + -1c = -4 + -3
Combine like terms: 3 + -3 = 0
0 + -1c = -4 + -3
-1c = -4 + -3
Combine like terms: -4 + -3 = -7
-1c = -7
Divide each side by '-1'.
c = 7
Simplifying
c = 7
U=5
x=1
z=-1.7
m=2
Trololololololo